Where We Stand With Precision Therapeutics in Myeloma: Prosperity, Promises, and Pipedreams - Pan, Darren; Richter, Joshua (Frontiers in Oncology, 2022)
Multiple myeloma remains an incurable disease despite numerous novel agents being approved in the last decade. Furthermore, disease behavior and susceptibility to current treatments often vary drastically from patient to patient. To date there are no approved therapies in myeloma that are targeted to specific patient populations based on genomic or immunologic findings. Precision medicine, using biomarkers descriptive of a specific tumor’s biology and predictive of response to appropriate agents, may continue to push the field forward by expanding our treatment arsenal while refining our ability to expose patients to only those treatments likely to be efficacious. Extensive research efforts have been carried out in this endeavor including the use of agents targeting Bcl2 and the RAS/MAPK and PI3K/AKT/mTOR pathways. Thus far, clinical trials have yielded occasional successes intermixed with disappointments, reflecting significant hurdles which still remain including the complex crosstalk between oncogenic pathways and the nonlinear genetic development of myeloma, prone to cultivating sub-clones with distinctive mutations. In this review, we explore the landscape of precision therapeutics in multiple myeloma and underscore the degree to which research efforts have produced tangible clinical results.